Pengaruh Penggunaan Media Interaktif Educaplay terhadap Motivasi Belajar IPAS Siswa Kelas IV SD Negeri 121 Salaonro Kecamatan Lilirilau Kabupaten Soppeng - Sudarto Sudarto; Abd. Kadir A; Arini Mulkisam (Celebes Science Education, 2026)
This study is a pre-experimental study with a One-Group Pretest-Posttest design. The aim is to determine whether the use of Educaplay interactive media has an effect or not on increasing the motivation to learn science in fourth-grade students at SDN 121 Salaonro. The population in this study were all of fourth-grade students at SDN 121 Salaonro, with a sample of 20 students selected using a saturated sampling technique. The data collection technique used was a questionnaire to measure the students' learning motivation before and after the treatment. The data analysis techniques used descriptive statistics and inferential statistics. Results: There was an increase in the average score of student learning motivation of 7.75 (pretest = 70.80 and posttest = 78.55), tcount = 7.077 > ttable = 1.729 at a significance level of 5%, indicating a significant difference in learning motivation before and after the use of Educaplay interactive media. Conclusion: The use of Educaplay interactive media has a positive effect on increasing the motivation to learn science at fourth-grade students at SDN 121 Salaonro.